One-Step Non-Reactive Spray Drying Approach to Produce Silicon/Carbon Composite-Based Hierarchically Structured Supraparticles for Lithium-Ion Battery Anodes. Issue 2 (1st February 2023) - Amin, Adil; Loewenich, Moritz; Kilian, Stefan O.; Wassmer, Theresa; Bade, Stefan; Lyubina, Julia; Wiggers, Hartmut; Özcan, Fatih; Segets, Doris
Abstract : A one-step non-reactive spray drying approach has been successfully demonstrated to produce hierarchically structured supraparticles of silicon/carbon composite nanoparticles synthesized in the gas-phase for Lithium-ion battery (LIB) anodes. The produced supraparticles combine the advantages of both nanoparticles and micrometer-sized particles: they inherit nanoparticle-like mechanical stability to resist pulverization but have a reduced surface area and therefore electrolyte contact area. The supraparticles showed very good redispersion stability when processed into electrodes and showed an improved density of the coated layer (increase by 19%) as compared to silicon/carbon composite nanoparticles. Furthermore, supraparticles exhibited a good first cycle Coulombic efficiency around 86% and a good cycling stability, i.e. 80% of the 3rd cycle capacity was retained after 126 cycles vs only 65.2% after the same number of cycles for the best coating from silicon/carbon composite nanoparticles. We consider this investigation as key finding for the scalable manufacturing of low-cost and dense Si-based anode materials for LIBs and at the same time as an example of how hierarchical electrode structures can make significant impact in electrochemistry.